Host specialization by reproductive interference between closely related herbivorous insects. Issue 2 (4th June 2015) - Nishida, Takayoshi; Takakura, Kohichi; Iwao, Keisuke
Abstract: Host specialization among closely related herbivores is common and is therefore a major theme in ecology. Despite its ecological importance, no general explanatory framework for host specialization is currently available. We introduce a new model of the evolution of host specialization in herbivorous insects. We use a two‐dimensional lattice comprising 32 × 32 cells. Moreover, the model incorporates reproductive interference, defined as any negative outcomes resulting from interspecific mating, between two species of herbivores feeding on two different host plants as well as ordinary resource competition and differences in host suitability. Our simulation showed that reproductive interference, together with other factors such as host‐related performance and resource competition, can actually drive the evolution of host specialization and thereby host partitioning between herbivorous insects during secondary contact. Host specialization arises particularly when levels of both reproductive interference and resource competition are intermediate. In contrast, host specialization seldom occurs if reproductive interference is absent. Thus, reproductive interference is as key to specialization as is spatial partitioning, which was not regarded as a realistic outcome when only resource competition was considered.